Constitutional and Administrative Aspects of the Ukraine's Medical Code - Мішина, Наталя Вікторівна; Мішина, Н. В.; Мишина, Наталья Викторовна; Mishyna, Natalia V.; Сурілова, Олена Олексіївна; Сурілова, О. О.; Сурилова, Елена Алексеевна; Surilova, Olena O. (Warsaw : Wydawnictwo «ALUNA», 2020)
Objective: The aim of this study is to show which aspects of Ukraine's constitutional and administrative law should appear in Ukraine's future medical code. Patients and methods: Materials and methods: The authors analyse five pieces of law or proposed law, including the 1996 Constitution's provisions on health care, Law the Fundamentals of Health Protection and the main codes. The authors apply classical legal analysis to these laws - analyzing the first three chapters of the proposed medical code from a constitutional and administrative perspective. The other methods used by the authors are systemic, comparative and synergetic. Conclusion: Conclusion: Ukraine needs a medical code incorporating international and European health care standards. Such a code will also further develop the country's medical legislation. Yet the proposed project has many constitutional and administrative weaknesses.

Мета цього дослідження - показати, які аспекти конституційного та адміністративного законодавства України мають бути включені до майбутнього Медичного кодексу України. Автори аналізують п’ять законів та запропонований закон, включаючи положення Конституції 1996 року про охорону здоров’я, Закон про основи охорони здоров’я та основні кодекси. Автори застосовують класичний юридичний аналіз до цих законів - аналізуючи перші три глави запропонованого Медичного кодексу з конституційної та адміністративної точки зору. Інші методи, якими користуються автори, є системними, порівняльними та синергетичними. Висновок: Україні потрібен Медичний кодекс, що включатиме міжнародні та європейські стандарти охорони здоров’я. Такий кодекс також сприятиме подальшому розвитку медичного законодавства країни. Проте запропонований проект має багато конституційних та адміністративних недоліків.

Цель этого исследования - показать, какие аспекты конституционного и административного законодательства Украины должны быть включены в будущий Медицинский кодекс Украины. Авторы анализируют пять законов и предложенный закон, включая положения Конституции 1996 года об охране здоровья, Закон об основах охраны здоровья и основные кодексы. Авторы применяют классический юридический анализ с этими законами - анализируя первые три главы предложенного Медицинского кодекса с конституционной и административной точек зрения. Другие методы, которыми пользуются авторы, являются системными, сравнительными и синергетическими. Вывод: Украине нужен Медицинский кодекс, включающий международные и европейские стандарты здравоохранения. Такой кодекс также будет способствовать дальнейшему развитию медицинского законодательства страны. Однако предложенный проект имеет много конституционных и административных недостатков.
Mishyna N. V. Constitutional and Administrative Aspects of the Ukraine's Medical Code / N. V. Mishyna, O. O. Surilova // Wiadomosci Lekarskie. – Warsaw : Wydawnictwo «ALUNA», 2020. – Т. 73 (1). – S. 191-195.
Keywords: health care reform; medical code; public health; right to the health care; right to the medical assistance; реформа охорони здоров’я; Медичний кодекс; охорона здоров'я; право на охорону здоров'я; право на медичну допомогу; реформа здравоохранения; Медицинский кодекс; здравоохранение; право на охрану здоровья; право на медицинскую помощь; Research Subject Categories::LAW/JURISPRUDENCE